2020
DOI: 10.3390/joitmc6040177
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Economy and Government

Abstract: We compared sharing economy development in 90 countries to demonstrate that higher qualities of government are associated with greater sharing economy growth. To explain this finding, we assumed that sharing economy benefits are enjoyed by the public, whereas its costs are chiefly borne by market incumbents. In considering these competing interests, policymakers tend to favor the latter as single-industry interests that can be more easily organized to influence policymaking. We then hypothesized that an electo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
(78 reference statements)
0
3
0
Order By: Relevance
“…It is a valuable tool for understanding the growth and impact of the sharing economy. This index has limitations that restrict its use [49][50][51].…”
Section: Sharing Economy Index To Investigate the Acceleration Of Sha...mentioning
confidence: 99%
“…It is a valuable tool for understanding the growth and impact of the sharing economy. This index has limitations that restrict its use [49][50][51].…”
Section: Sharing Economy Index To Investigate the Acceleration Of Sha...mentioning
confidence: 99%
“…Focusing on Airbnb for this study ensured that a diverse range of employees in different roles, functions, and teams, as well as seniority levels in multiple offices worldwide, would be considered. With its growing popularity and exponential business growth, Airbnb has been the focus of discussion among practitioners and scholars alike [24][25][26]. Belarmino and Koh [27] conducted a systematic review of previous studies that examined peer-to-peer accommodations and found that the human resources topic had not been explored in previous literature.…”
Section: Airbnb and Tourism And Services Sectormentioning
confidence: 99%
“…Airbnb serves as an illustration of the hospitality industry's turmoil. The company, famous for its platform offering unique accommodations, experienced a severe downturn during the pandemic [33][34][35][36][37][38][39][40][41]. Travel fears and restrictions dramatically reduced demand for shared lodging services, leading to a 67% decrease in Airbnb's revenues in 2020 [41].…”
Section: Covid-19 and The Hospitality Sectormentioning
confidence: 99%